Capitalism: A Conversation in Critical Theory - Fraser, Nancy; Jaeggi, Rahel (John Wiley & Sons, 2018)
In this important new book, Nancy Fraser and Rahel Jaeggi take a fresh look at the big questions surrounding the peculiar social form known as “capitalism,” upending many of our commonly held assumptions about what capitalism is and how to subject it to critique. They show how, throughout its history, various regimes of capitalism have relied on a series of institutional separations between economy and polity, production and social reproduction, and human and non-human nature, periodically readjusting the boundaries between these domains in response to crises and upheavals. They consider how these “boundary struggles” offer a key to understanding capitalism’s contradictions and the multiple forms of conflict to which it gives rise. What emerges is a renewed crisis critique of capitalism which puts our present conjuncture into broader perspective, along with sharp diagnoses of the recent resurgence of right-wing populism and what would be required of a viable Left alternative. This major new book by two leading critical theorists will be of great interest to anyone concerned with the nature and future of capitalism and with the key questions of progressive politics today.
Philosophy; Political Science
Keywords: boundary struggle; capitalism; political philosophy; triple movement

Karl Polanyi in Dialogue: A Socialist Thinker for our Times - Brie, Michael (Black Rose Books, 2017)
Featuring essays from Michael Brie (Rose Luxemburg Foundation, Berlin), Nancy Fraser (New School for Social Research, New York) and Kari Polanyi-Levitt (McGill University, Montreal). The contemporary Left fights its political battles on various fronts: protesting the crippling structural inequalities that sustain neoliberal economic policy; developing sustainable, community-based alternatives to the consumerism and short-termism that exacerbate the environmental crisis; and advocating for the cultural recognition, emancipation and celebration of the diversity and pluralism of human identity. But despite this versatility the Left appears to be in worldwide retreat whilst an aggressive new ‘Alt-Right’ is taking to the internet and the streets, regurgitating a regressive and patriarchal vision of society that has already won startling political victories in the US and Europe. Amidst the vertiginous tension of such a crisis, Michael Brie argues for an urgent theoretical and practical reorganisation of the Left. Developing the work of philosopher and social theorist Karl Polanyi, Brie advocates an alliance of socialist liberals and libertarian ‘commonists’ that unites contemporary campaigns for recognition, difference and human dignity with more traditional struggles for social welfare and economic democracy. Starting with Nancy Fraser’s critical reappraisal of Polanyi in her article “A Triple Movement? Parsing the Politics of Crisis after Polanyi” (included), Brie powerfully reinterprets Polanyi’s thought for present times, developing concrete proposals for a Polanyian political response to neoliberalism, an ascendent authoritarian right and the ongoing threat of global ecological disaster. Also included are two articles by Polanyi translated into English for the first time and Kari Polanyi-Levitt’s lecture at the Rosa Luxemburg Foundation “From the Great Transformation to the Great Financialisation”.
Philosophy; Political Science
Keywords: biography; ecology; economics; feminism; history; labor; labour; politics; racism; sociology

Le religioni della politica: Fra democrazie e totalitarismi - Gentile, Emilio (Gius.Laterza & Figli Spa, 2014)
La sacralizzazione della politica accade ogni volta che un'entità politica – la nazione, la democrazia, lo Stato, la razza, la classe, il partito, il movimento – è trasformata in una entità sacra, in un oggetto di devozione e di culto, ed è collocata al centro di un sistema di credenze, di simboli e di riti. Nascono allora le religioni della politica, che non si identificano con un unico tipo di ideologia e di regime: esse possono sacralizzare la democrazia o l'autocrazia, l'eguaglianza o la disuguaglianza, la nazione o l'umanità.
Philosophy
Keywords: essence of fascism; fascism; history / modern / 21st Century; political philosophy

The Passage West: Philosophy After the Age of the Nation State - Marramao, Giacomo (Verso Books, 2014)
In this ambitious work, Giacomo Marramao proposes a radical reconceptualization of the world system in our era of declining state sovereignty. He argues that globalization cannot be reduced to mere economics or summarized by phrases such as ‘the end of history’ or the ‘westernization of the world’. Instead, we find ourselves embarking on a passage to a new, post-nation state age destined to transform all civilizations – and to disrupt Western geopolitical dominance. To confront the challenges of this interregnum one must think in terms of a new and radical universalism, a universalism of difference able to revitalize politics and to demythologize identity.Building on the great interwar discussion between Spengler, Junger, Schmitt and Heidegger, Marramao’s new work engages with Habermas, Derrida and post-colonialism. Arguing against the classic Western pretension to universal norms of democracy and reason, he develops instead the idea of a ‘universal politics of difference’. KM - contains chapter: Gift, exchange, obligation: Karl Polanyi and social philosophy
Philosophy; Political Science
Keywords: exchange; international relations; religious philosophy; social philosophy

Fortunes of Feminism: From State-Managed Capitalism to Neoliberal Crisis - Fraser, Nancy (Verso Books, 2013)
Charts the history of women’s liberation and calls for a revitalized feminism.Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.During the ferment of the New Left, “Second Wave” feminism emerged as a struggle for women’s liberation and took its place alongside other radical movements that were questioning core features of capitalist society. But feminism’s subsequent immersion in identity politics coincided with a decline in its utopian energies and the rise of neoliberalism. Now, foreseeing a revival in the movement, Fraser argues for a reinvigorated feminist radicalism able to address the global economic crisis. Feminism can be a force working in concert with other egalitarian movements in the struggle to bring the economy under democratic control, while building on the visionary potential of the earlier waves of women’s liberation. This powerful new account is set to become a landmark of feminist thought.
Philosophy; Political Science
Keywords: critical theory; feminism; feminist theory; triple movement

Karl Polanyi and the Contemporary Political Crisis: Transforming Market Society in the Era of Climate Change - Kirby, Peadar (Bloomsbury Publishing, 2020)
Has politics reached breaking point? Rather than defending liberalism or abandoning it, how can a socially just and ecological alternative be built? Peadar Kirby investigates the causes of our current multifaceted global crisis by drawing on the work of Karl Polanyi. This book explores Polanyi's theory that social disruptions result from the attempt to run society according to the rules of the market. Drawing on these ideas, it outlines pathways towards an alternative future that overcome weaknesses in Marxism. Linking the ecological, political and socio-economic crises, Kirby identifies that an alternative socio-ecological model is emerging, consistent with the insights of Polanyi. Karl Polanyi and the Contemporary Political Crisis is an urgent intervention into key debates on the future of politics, on the low-carbon transition, on automation and on the emerging world order.
Keywords: climate change; ecological crisis